Hydrolyzed corn starch with maltotetraose for skin defense through NRF2 pathway activation in human keratinocytes - Hitomi Hagawa; Eri Ichikawa; Keiko Otake; Mayuko Ishii; Naoko Kawaguchi (PLoS ONE, 2026)
Oxidative stress, which can be triggered by various external stimuli, such as ultraviolet radiation and pollution, compromises skin health, accelerates aging and skin disorders, and impacts quality of life. This study investigated the potential of hydrolyzed corn starch containing maltotetraose in skin defense through nuclear factor erythroid 2-related factor 2 (NRF2) pathway activation in human keratinocytes. Using DNA microarray analysis and assessing key antioxidant-responsive genes, we evaluated the capacity of this ingredient to enhance cellular defense mechanisms. Human keratinocytes treated with it demonstrated significant upregulation of antioxidant-responsive genes, including HMOX1 , GPX2 , and NQO1 , which are known targets of NRF2. These findings were corroborated by western blotting and immunostaining analyses, which confirmed increased NRF2 protein expression and NRF2 nuclear translocation. Moreover, fluorescence assays and microscopy showed that treatment with the ingredient effectively reduced reactive oxygen species levels in keratinocytes exposed to oxidative stress. These results suggest that activation of the NRF2 pathway by this ingredient enhances the cellular antioxidative response and reduces reactive oxygen species levels in keratinocytes. This NRF2-mediated antioxidative activity positions hydrolyzed corn starch containing maltotetraose as a promising ingredient for cosmetic products, with potential implications for improving skin health, reducing pigmentation, and combating aging. However, these effects were not directly evaluated in this study. Future studies are warranted to evaluate its efficacy in vivo.